Influence of operating factors on lubrication mode and wear resistance of parts of diesel engines of cars - Диха, О. В.; Аулін, В.В.; Лисенко, С.В.; Гриньків, А.В. (Problems of Tribology, 2019)
It is established that in the real conditions of operation characteristic of simultaneous action of different types of wear, the relationship of which depends on the design, technology of manufacturing parts, the quality of used lubricants and the load of friction. When describing the processes of wear, it is believed that the wear rate depends on the type of lubrication, but to assess the wear resistance of the parts and connections of the diesel engine, it is necessary to know the whole spectrum of patterns of development and degradation of processes and states. It is shown that in order to assess the quality of lubricants on the basis of their operational properties, it is expedient to use the test scheme: four-headed pyramid, cone-three balls and devices for heating the oil and measuring the width of the trace of wear of the conical surface. In order to optimize the composition of the additive in motor oil, the mathematical planning of the experiment was used and the method of its implementation was developed for rootable planning of the second order. According to the mathematical planning of the experiment, a regression mathematical model of wear intensity was obtained, optimal parameters were determined: the content of the additive - 2,2 %; lubricating fluid temperature - 50 °С; the contact pressure is 10 MPa and the model is checked for adequacy